Healthy Lifestyle Beliefs Scale: Psychometric properties in Portuguese pregnant women - Nunes, Maria A.; Almeida, Sofia; Cardoso, Alexandrina; Vieira, Margarida; Melnyk, Bernadette M. (Research in nursing & health, 2023)
Healthy lifestyle during pregnancy influences the pregnant woman's and child's physical and mental health, impacting perinatal outcomes. Healthy lifestyle beliefs are predictors of lifestyle behaviors, requiring a valid and reliable instrument to assess them during prenatal care. The 16‐item Healthy Lifestyle Belief Scale (HLBS) measures a person's beliefs about their ability to live a healthy lifestyle. This study aimed to examine the psychometric properties of a Portuguese version of the HLBS among pregnant women. A methodological study was developed in two phases: cross‐cultural adaptation and evaluation of the psychometric properties of the Portuguese version in a nonprobability sample of 192 Portuguese pregnant women. The exploratory factor analysis suggested three subscales, which explained 53.8% of the total variance. Cronbach's α was 0.83 for the overall scale and for the subscales ranged between 0.71 and 0.81. The HLBS is a reliable and valid instrument to assist health professionals in assessing the ability of Portuguese pregnant women to adopt a healthy lifestyle. Assessing healthy lifestyle beliefs potentially contributes to the development of health behavior interventions in pregnant women and consequently improves perinatal outcomes through evidence‐based practices.